A Double-Coil TMS Method to Assess Corticospinal Excitability Changes at a Near-Simultaneous Time in the Two Hands during Movement Preparation - Wilhelm, Emmanuelle; Quoilin, Caroline; Petitjean, Charlotte; Duque, Julie (Frontiers in Human Neuroscience, 2016)
Background: Many previous transcranial magnetic stimulation (TMS) studies have investigated corticospinal excitability changes occurring when choosing which hand to use for an action, one of the most frequent decision people make in daily life. So far, these studies have applied single-pulse TMS eliciting motor-evoked potential (MEP) in one hand when this hand is either selected or non-selected. Using such method, hand choices were shown to entail the operation of two inhibitory mechanisms, suppressing MEPs in the targeted hand either when it is non-selected (competition resolution, CR) or selected (impulse control, IC). However, an important limitation of this “Single-Coil” method is that MEPs are elicited in selected and non-selected conditions during separate trials and thus those two settings may not be completely comparable. Moreover, a more important problem is that MEPs are computed in relation to the movement of different hands. The goal of the present study was to test a “Double-Coil” method to evaluate IC and CR preceding the same hand responses by applying Double-Coil TMS over the two primary motor cortices (M1) at a near-simultaneous time (1 ms inter-pulse interval). Methods: MEPs were obtained in the left (MEPLEFT) and right (MEPRIGHT) hands while subjects choose between left and right hand key-presses in blocks using a Single-Coil or a Double-Coil method; in the latter blocks, TMS was either applied over left M1 first (TMSLRM1 group, n=12) or right M1 first (TMSRLM1 group, n=12). Results: MEPLEFT were suppressed preceding both left (IC) and right (CR) hand responses whereas MEPRIGHT were only suppressed preceding left (CR) but not right (IC) hand responses. This result was observed regardless of whether Single-Coil or Double-Coil TMS was applied in the two subject groups. However, in the TMSLRM1 group, the MEP suppression was attenuated in Double-Coil compared to Single-Coil blocks for both IC and CR, when probed with MEPLEFT (elicited by the second pulse). Conclusions: Although Double-Coil TMS may be a reliable method to assess bilateral motor excitability provided that a RM1-LM1 pulse order is used, further experiments are required to understand the reduced MEPLEFT changes in Double-Coil blocks when the LM1-RM1 pulse order was used.